Geographic and environmental impacts on gut microbiome in Himalayan langurs (Semnopithecus schistaceus) and Xizang macaques (Macaca mulatta vestita) - Wang, Xueyu; Li, Hong; Yang, Yumin; Wu, Zhijiu; Wang, Zhixiang; Li, Dayong; Xia, Wancai; Zou, Shuzhen; Liu, Yujia; Wang, Fan (Frontiers in Microbiology, 2024)
Gut microbiome plays a crucial role in the health of wild animals. This study investigated the gut microbiome of Himalayan langurs (Semnopithecus schistaceus) and Xizang macaques (Macaca mulatta vestita) across different geographic regions using 16S rRNA gene and metagenomic sequencing. Results showed distinct clustering patterns in gut microbiota based on geographic location. Soil had an insignificant impact on host gut microbiome. Himalayan langurs from mid-altitude regions exhibited higher levels of antibiotic resistance genes associated with multidrug resistance, while Xizang macaques from high-altitude regions showed a broader range of resistance genes. Variations in carbohydrate-active enzymes and KEGG pathways indicated unique metabolic adaptations to different environments. These findings provide valuable insights into the health and conservation of these primates and the broader implications of microbial ecology and functional adaptations in extreme conditions.